Multimodality imaging evaluation of nasal sinus alveolar rhabdomyosarcoma: Two case reports - Huang, Wenpeng; Zhang, Yongbai; Gao, Ge; Li, Liming; Yang, Qi; Qiu, Yongkang; Kang, Lei (Frontiers in Medicine, 2022)
Background: Rhabdomyosarcoma (RMS) is a common pleomorphic malignant soft tissue sarcoma in children and adolescents that originates from rhabdomyoblasts or mesenchymal precursor cells. Alveolar rhabdomyosarcoma (ARMS) mostly occurs in adolescents aged 10 to 15 years old and is characterized by more aggressive behaviors and worse prognosis than other sarcomas, prone to lymphatic and hematogenous metastasis in the early stage as well as metastasizing to breast, testis, pancreas, and other parts. ARMS often occurs in the limbs and genitourinary system, however, head and neck ARMS are relatively rare when involving the nasal cavity or sinuses. The role of MRI and 18F-FDG PET/CT remains to be established in ARMS. Case Report: Case 1: An 18-year-old male was found with a left submandibular mass of approximately 1 cm in diameter 2 months ago, which gradually increased in size. CT showed multiple soft tissue masses in maxillofacial and neck regions and the lesions invaded the frontal lobe and the inner wall of the left orbital lobe. MRI showed the masses with hypointensity on T1WI, hyperintensity on T2WI, and DWI with significant enhancement. 18F-FDG PET/CT showed multiple hypermetabolic lesions located in the maxillofacial, neck regions, 3rd lumbar vertebra, and the right sacrum. Case 2: A 14-year-old male presented with left maxillary pain with nasal congestion and left ocular swelling 15 days ago. CT demonstrated a soft tissue mass in the nasal cavity and sinuses with local protrusion into the left orbit. MRI showed the masses with a slightly low signal on T1WI, high signal on T2WI, and DWI with significant heterogenous enhancement. 18F-FDG PET/CT showed hypermetabolic lesions in the left maxillofacial and neck regions. Conclusion: Nasal sinus ARMS is highly malignant with a poor prognosis. Accurate diagnosis relies not only on histopathology and immunohistochemistry examination but also on genetic detection of characteristic chromosomal translocations and fusion genes. Imaging methods such as MRI and PET/CT can accurately assess the extent of the lesions and metastases, assist the diagnosis of the disease and the selection of treatment regimens, provide precise localization for surgery, and help with treatment monitoring and follow-up.